Persepsi Konsumen Mengenai Suasana Lingkungan Toko Ritel Terhadap Ketertarlkan Pelanggan Toko Ritel - Khusniyah Purwani (Jurnal Aplikasi Bisnis, 2017)
The focus of this research reveal the perceptions of retail customers to see the environmental atmosphere shop to shop choices that will ultimately affect the interest of customers shop. Indicators store environment seen through social factors, store design and in-store music. Store selection criteria will be detailed through consumer perceptions of service clerks, quality of merchandise, money (as seen from monetary units), cost (time and effort), and psychic costs of consumers. These factors affect the perception of consumers about the value of the merchandise sold in stores as well and at a late stage will affect the interest of customers shop.A total of 190 respondents spread across various retail stores In Yogyakarta Special Region in the survey using a questionnaire. Most respondents who netted the students or students. Field survey methods used to collect data and data analysis using structural equation modeling-analysis of moment structures (AMOS). AMOS though results beginning with the confirmatory factor analysis showed that the goodness of fit test of this model fit, so this research model is acceptable. Causality test results indicate that the hypothesis of significant eleven and nine hypotheses were not significant. So it can be concluded that, overall, the hypothesis proposed in this study proved.